Prototipe Model Pembelajaran Adabul Muta’allim Untuk Meningkatkan Karakter Siswa - Suardi M (Journal on Education, 2023)
Teaching conducted by the teacher can only be practical if using a learning model that suits their needs, as well as learning that can only be effective if the learning model applied by the teacher is in accordance with the needs of students, so research and development of this learning model, based on the results of the teacher's needs analysis and students that have been carried out by previous researchers. In research and development it is known that it has several stages until a model can be said to be complete and can be used, but because in this study it is only limited to a hypothetical model or pre-model design stage, the researcher only presents a big picture of the components of the adabul muta'allim learning model, which based on descriptive analysis of the results of the previous needs analysis. The results of developing a hypothetical model of this model describe the syntax of the model starting from motivation, exploration, participatory learning, investigation, conception, review, and the final stage is assessment. In addition, it also describes the social system, support system, reaction principle, as well as the instructional impact and the accompanying impact of the adabul muta'allim learning model which is expected to improve student character. Furthermore, the resulting hypothetical model prototype can be continued at the model design (product) stage, then followed up with the validation test stage by experts, and practicality by users to test the effectiveness of students.